L-band mode-locked fiber laser delivering adjustable bright and dark pulses with erbium zirconia yttria aluminum co-doped fiber - Markom, A.M.; Paul, M.C.; Dhar, A.; Das, S.; Yasin, M.; Apsari, R.; Ahmad, Harith; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2016)
We demonstrate the generation of adjustable bright and dark pulses from Erbium Zirconia Yttria Aluminum co-doped fiber (Zr-EDF) incorporated fiber ring laser with net anomalous dispersion. The fiber enhances the birefringence and nonlinearity of the laser cavity to produce a mode-locked pulse train operating at a relatively low pump threshold of 70 mW. Domain-wall dark pulses repeated at the fundamental cavity frequency is observed by adjusting the intra-cavity polarization state. The pulse repetition rate was maintained at 14.1 MHz throughout the dark pulse operation. It operates at 1601 nm with the pulse energy of 14.2 pJ at pump power of 70 mW. Besides, the dark pulse operation was demonstrated at high stability with SNR of 33 dB.